Flight dynamics and system identification for modern feedback control : avian-inspired robots - Grauer, Jared A. (Woodhead Publishing in mechanical engineering., 2013)
This title covers flapping-wing aircraft and flight dynamics and nonlinear, multibody modelling as well as flight testing and instrumentation, system identification from flight test data, and feedback control and linearization.